2022
DOI: 10.3390/nu14132662
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Dietary Inflammatory Index and Gastric Disease Risk: Findings from a Korean Population-Based Cohort Study

Abstract: Evidence suggests that diets with high pro-inflammatory potential may play a substantial role in the origin of gastric inflammation. This study aimed to examine the association between the energy-adjusted dietary inflammatory index (E-DIITM) and gastric diseases at baseline and after a mean follow-up of 7.4 years in a Korean population. A total of 144,196 participants from the Korean Genome and Epidemiology Study_Health Examination (KoGES_HEXA) cohort were included. E-DII scores were computed using a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The total score of the DII was −8.20 to +6.36 in Korean population cohorts. 30 Median (Standard Deviation, SD) and range of the Energy Adjusted DII (E-DII) in the Mitchelstown cohort were −1.40±0.1 and −5.10 to +3.68. 34 A study from Xiangya Hospital [Xiangya, Hunan Province] calculated that the average E-DII was +0.68± 0.08, and the score ranged from –5.32 to +4.26, but the study population was Americans.…”
Section: Discussionmentioning
confidence: 99%
“…The total score of the DII was −8.20 to +6.36 in Korean population cohorts. 30 Median (Standard Deviation, SD) and range of the Energy Adjusted DII (E-DII) in the Mitchelstown cohort were −1.40±0.1 and −5.10 to +3.68. 34 A study from Xiangya Hospital [Xiangya, Hunan Province] calculated that the average E-DII was +0.68± 0.08, and the score ranged from –5.32 to +4.26, but the study population was Americans.…”
Section: Discussionmentioning
confidence: 99%
“…(36) Estrogen hormones regulate mucosal secretion, protect the mucosa from acid-induced damage, and regulate the growth and expression of gastric cells, thereby reducing the risk of gastric inflammation Estrogen regulates human duodenal bicarbonate secretion and reduces the risk of ulcers and gastric disease in females, and a decrease in the level of estrogen induces a depletion in the mucosal defense function. (37) Previous research indicated that females experience lower oxidative stress than males. (38) according to C. Kerksick et al Animal experiments had shown that female sex hormones have a strong anti-ulcer effect and to promote ulcer healing associated with medications (indomethacin, aspirin) that may protect female sex hormones from mucosal damage as an estrogen has been shown to reduce its occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Never-smokers included individuals who had either never smoked or had smoked fewer than 100 cigarettes in their lifetime. Now-smokers were participants who had smoked at least 100 cigarettes in their lifetime and reported consuming a non-zero number of cigarettes per day within the past 30 days 8 . Alcohol drinking status was classified into four distinct categories, reflecting their alcohol consumption patterns: Never drinkers (lifetime abstainers), former drinkers (abstinent within the past year), moderate drinkers (1 or 2 drinks per day for females/males, respectively), and heavy drinkers (>1 or >2 drinks per day for females/males, respectively, and/or frequent binge drinking) 11 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Lifestyle choices such as smoking and excessive alcohol consumption contribute to heightened oxidative stress in individuals infected with H. pylori 7 . Furthermore, existing evidence suggests that specific dietary behaviors, characterized by the consumption of nutritionally suboptimal foods, are correlated with an increased risk of contracting H. pylori 8 . Furthermore, numerous studies have explored the correlation between oxidative stress and mortality.…”
Section: Introductionmentioning
confidence: 99%